TEKNIK SUPERVISI AKADEMIK DI SEKOLAH ISLAM - Paramudita, Alfiyan; Ridwan, iwan (Madrasa: Journal of Islamic Educational Management, 2019)
Academic supervision carried out by the headmaster is done only once in a semester. The lack of implementation of guidance of school principals on educators in the preparation of design of learning implementation, mastery and delivery of teaching materials. This study aims to uncover the processes of planning, implementing, and evaluating the academic supervision at Al-Aqsha Jatinangor Junior High School plus, West Java, Indonesia. The research method used is qualitative. The results of the study show that (1) Academic supervision in Al-Aqsa Junior High School plus is planned using individual and group techniques carried out within one year; (2) implementation of academic supervision with individual techniques monitored through surveillance cameras that have been installed in each class. Individual supervision of 46 educators involved 4 senior teachers namely Apit Miftahudin, Oih Baihaqi, Apip Hadi Susanto, and Saidiman; (3) supervision evaluation is carried out at the end of semester meeting together with the entire academic community of the Al-Aqsa Junior High School plus. Focus on follow-up training on academic supervision results at the Al-Aqsa Junior High School plus regarding instrument learning devices;